CuCo2O4 nanowall morphology as Li-ion battery anode: Enhancing electrochemical performance through stoichiometry control - Bhardwaj, M.; Suryawanshi, A.; Fernandes, R.; Tonda, S.; Banerjee, A.; Kothari, D.; Ogale, S. (Materials Research Bulletin, 2017)
We have employed template-free synthesis of CuCo2O4 (CCO) system to achieve unique ultrathin porous nanowall type morphology, and evaluated for Li-Ion battery anode application. We observe that under the hydrothermal growth a starting stoichiometric mixture of cationic precursor's leads to a bi-phasic constitution comprising of defect-spinel CCO and a small quantity of CuO. Use of the excess but optimum cobalt in the precursor mix leads to single phase defect-spinel. We have carefully examined the implications of off-stoichiometry for different cases of interest (including the case of Cu-excess) for morphology, microstructure, the physical/electrochemical properties, and the evolution of the Li-ion battery anode under cycling for different active materials loading. In case of optimum Cu excess based CCO renders an impressive performance as Li-ion battery anode with high rate performance, 836 mAh g−1 and 757 mAh g−1 at 1.25C and 2.5C, respectively, and good cycling stability. © 2016 Elsevier Ltd